ANALISIS KINERJA BONGKAR MUAT BARANG DALAM UPAYA MENINGKATKAN ARUS TERMINAL PETI KEMAS PALARAN DI KOTA SAMARINDA - FAUZAN, DIO AULIA (KURVA S JURNAL MAHASISWA, 2017)
Palaran container terminal is located in Kelurahan Bukuan Sub District Palaran Kota Samarinda East Kalimantan. Working on PT Pembangunan Perumahan (Persero) Tbk since June 2008, the container port worth Rp 261 billion was completed in May 2010. After undergoing the test, the terminal or container port was officially declared operational in September 2010. To manage it, PT Samudera Indonesia Tbk To its new subsidiary, PT Pelabuhan Samudera Palaran.                As the Jakarta Municipal container terminal in PT PP, the Palaran container terminal is also a new one hundred percent port, starting from scratch. Not the result of upgrading the old port. Featuring a 270 meter dock, this new container terminal is equipped with a 70,200 square meter piling-up field, and has two cranes for container loading and unloading. Located in Bukuan Village, Palaran Subdistrict, this new container terminal is just 5 kilometers to the east of Samarinda Port. From the office of the Governor of East Kalimantan located on the edge of Mahakam, in downtown Samarinda, the distance is only about 9 kilometers.                With such large volume growth, the current port capacity will not be sufficient, so a new port with a larger capacity is needed. The realization of this project begins with the tender process of development and operation of the terminal with the schemeBOT (Built, Operate & Transfer) for 50 years organized by Pelindo IV and Samarinda City Government, which was won by PT Samudera Indonesia, Tbk. Furthermore, Special Purpose Company (SPC) was established, PT Palabuhan Samaran Ocean to build and operate TerminalFairholder Container for 50 years.                From the results of performance analysis shows that the BOR tends to decline throughout the year since 2001. The lowest BOR achieved in 2016 amounted to 32.2%. The highest BOR was achieved in 2013 of 35.7%. Both the lowest and highest BOR are still below the value provided by UNCTAD, which is 50%. Compared to container crane capacity of 1,468,900 TEUs / year, and RTE capacity of 1,113,900 TEUs / year, the prediction rate is still very far.